1995
DOI: 10.1093/humrep/10.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thromboembolism in relation to an in-vitro fertilization programme: three case reports

Abstract: Severe thrombotic events following ovarian stimulation for in-vitro fertilization (IVF) procedures in three women are reported. None of these patients presented any concomitant clinical sign of ovarian hyperstimulation syndrome. Coagulation inhibitors were in the normal range but cardiovascular risk factors were present. It is postulated that early thrombosis could be favoured by high endogenous plasma oestrogen concentrations subsequent to ovarian stimulation when associated with another risk factor. Our data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 0 publications
0
25
0
5
Order By: Relevance
“…Data regarding the frequency of VTE, however, comprise predominantly of case reports, case series, and relatively small cohort studies (Table S6). [116][117][118][119][120][121] In two large retrospective series of patients undergoing in vitro fertilization, thrombosis complicated 0.1% (95% CI, 0%-0.3%) 116 and 0.3% (95% CI, 0%-0.8%) 117 of cycles. A hospital-based case-control study demonstrated a fourfold increase in antenatal VTE with assisted reproductive technology for singleton pregnancies and a sixfold incidence in twin pregnancies but no statistically signifi cant association with postpartum VTE.…”
Section: Vte In Patients Using Assistedmentioning
confidence: 99%
“…Data regarding the frequency of VTE, however, comprise predominantly of case reports, case series, and relatively small cohort studies (Table S6). [116][117][118][119][120][121] In two large retrospective series of patients undergoing in vitro fertilization, thrombosis complicated 0.1% (95% CI, 0%-0.3%) 116 and 0.3% (95% CI, 0%-0.8%) 117 of cycles. A hospital-based case-control study demonstrated a fourfold increase in antenatal VTE with assisted reproductive technology for singleton pregnancies and a sixfold incidence in twin pregnancies but no statistically signifi cant association with postpartum VTE.…”
Section: Vte In Patients Using Assistedmentioning
confidence: 99%
“…Arousseau et al 7 relataram três casos graves de tromboembolismo em pacientes submetidas à FIV sem evidência clínica de SHO: uma paciente apresentou embolia pulmonar, outra trombose de carótida e a terceira isquemia mesentérica.…”
Section: Discussionunclassified
“…As alterações na coagulação sangüínea são pouco freqüentes nestas situações, porém, nos casos de hiperestimulação folicular, especialmente na síndrome de hiperestimulação ovariana (SHO), onde há uma hipersecreção de estrogênios, a repercussão sobre o sistema vascular pode ser significativa [3][4][5][6] . O repouso que estas pacientes normalmente são submetidas, associado à possibilidade de alterações no equilíbrio hemostático, tornam essas mulheres muito propensas aos fenômenos tromboembólicos 7,8 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…O diagnóstico na maioria dos casos tem sido feito por laparotomia 8,15 . Em 1-2% das fertilizações in vitro pode ocorrer aumento do risco de TEV em sítios não usuais (sistema nervoso central, membros superiores) e muitas vezes há trombofilia subjacente, sobretudo fator V Leiden 16 . O esquema de investigação da TVP na gestação é apresentado na Figura 1.…”
Section: Os Testes Diagnósticos Podem Ser Não Invasivos (Ultrassom [Uunclassified